VICTIM TRUST FUND DALAM TINDAK PIDANA KEKERASAN SEKSUAL - Yuliani Catur Rini; Muhammad Mirza Habibie (Faculty of Social, Economics and Humanities, 2022)
Cases of sexual violence in Indonesia are increasing every year, even the victims are not only adults, teenagers, children and even toddlers are now the targets. The increasing number of cases of sexual violence is not only seen in terms of quantity or number of cases, but also in terms of quality. For this reason, the state is present with its policy, then Law Number 12 of 2022 concerning the Crime of Sexual Violence (UU TPKS) is passed which aims to protect every citizen from violence and degrading treatment of human dignity. The Victim Trust Fund or Victim Assistance Fund is a mandate from the TPKS Law as a form of state responsibility when the assets of the confiscated convict are insufficient for restitution costs. The Victim Assistance Fund exists as the state exists to protect its citizens, the concept of the Victim Trust Fund was previously regulated in Presidential Regulation No. 80 of 2011 concerning Trust Funds. However, the Presidential Regulation does not specifically regulate the aid fund for victims of sexual violence. The purpose of this study is to provide a legal framework on how to manage the Victim Aid Fund using a conceptual approach that uses analytical deductive methods to process data. The Victim Assistance Fund should be managed by the Witness and Victim Protection Agency (LPSK) which already has a system so that the state can save costs in establishing a new institution.